Assessment of the Anti-inflammatory and AnalgesicProperties of Tragia involucrate Anti-inflammatory, AnalgesicActivity of Tragia involucrata (Journal of Laboratory Animal Science, 2025)
The diverse bioactive properties of Tragia involucrate are highlighted by numerous studies that reveal its anti-inflammatory,  antioxidant, analgesic, and potential anti-diabetic effects. Leaves of T. involucrata were gathered, extracted with various  solvents, and analyzed for phytochemical components through biochemical methods and high-performance thin layer chromatography (HP-TLC). The extracts underwent evaluation for cytotoxicity, antioxidant capacity, and in vitro  anti-inflammatory effects. An acute oral toxicity assessment was conducted to determine in vivo toxicity in rats, while  carrageenan-induced paw edema was utilized to assess in vivo anti-inflammatory activity. The phytochemical constituents  include tannins, flavonoids, saponins, terpenoids, and steroids. Notably, the aqueous extract exhibited significant  membrane-stabilizing effects on human red blood cell membranes and demonstrated potent activity against stable free  radicals. Results from acute toxicity studies and paw edema tests indicated that the extract was well tolerated at a dose  of 2000 mg/kg body weight and effectively reduced edema. Additionally, the aqueous extract produced analgesic effects  at an oral dosage of 300 mg/kg body weight. These results imply that AETI possesses promising analgesic, antioxidant,  and anti-inflammatory properties, suggesting that T. involucrata may be a therapeutic option for managing pain and  inflammation.
Keywords: Tragia involucrata; anti-inflammatory; analgesic; antioxidant activity; Ayurveda